Right lower limb lymphatic aplasia in lymphoscintigraphy: a case report - Prayash Paudel; Neetika Paudel; Manish Timalsina (Journal of Medical Case Reports)
Abstract Background Primary lymphedema, affecting 1.15 per 100,000 individuals, under 20 years is rare. It includes three types: major vessel abnormalities, congenital lymphatic valvular incompetence or aplasia, and lymph node fibrosis. This condition arises from inherent lymphatic abnormalities and can be linked to genetic mutations causing valvular dysfunction, hypoplasia, or aplasia. Clinically, it can be isolated or syndromic and can present as Milroy’s disease or Meige’s disease depending on onset and associated features. Lymphoscintigraphy often reveals aplasia (14%) or hypoplasia (56%). In this case, lymphoscintigraphy indicated right lower limb aplasia correlating with clinical findings of limb swelling. This is one of the very few cases of lymphatic aplasia confirmed by lymphoscintigraphy. Management involves a multidisciplinary team approach, focusing on symptom control and patient education, as the condition is incurable but manageable. Case presentation This is a case report of a 14-year-old boy from Southern Nepal with right limb swelling since birth and progressive scrotal and penile swelling for 7 years. Examination showed unilateral, painless non-pitting edema in the right leg, scrotum, and penile shaft. Imaging showed abdominal and left inguinal lymphadenopathy. Left inguinal lymph node biopsy indicated capillary hemangioma. Lymphoscintigraphy confirmed primary lymphatic aplasia with absent lymphatic channels in the right lower limb. Treatment focused on physiotherapy for symptom management, with regular monitoring. Conclusion Diagnosis of primary lymphedema is necessary for timely intervention to halt the progression and prevent complications. The most sensitive method of diagnosis is lymphoscintigraphy, with its advantage over conventional methods.